Remediation and resource utilization of Cr(Ⅲ), Al(Ⅲ) and Zr(Ⅳ)-containing tannery effluent based on chitosan-carboxymethyl cellulose aerogel - Shuang Liang; Xuechuan Wang; Chao Wei; Long Xie; Zhongming Song; Xugang Dang (Journal of Bioresources and Bioproducts)
Composite aerogel based on sodium carboxymethyl cellulose (CMCNa) and chitosan (CS), i.e., CS/CMCNa, was prepared through a sol-gel method. Then, CS/CMCNa was used for simulating the adsorption of metal ions (Cr3+, Al3+ and Zr4+) produced by the tanning industry. The adsorption process is consistent with the Langmuir isotherm adsorption model and pseudo-second order kinetics. The maximum fitted adsorption capacities of Cr3+, Al3+, and Zr4+ could reach 250.0, 111.1, and 100.0 mg/g, respectively. After metal ion adsorption, the obtained composite materials (CS/CMCNa-Cr3+, CS/CMCNa-Al3+, and CS/CMCNa-Zr4+) were used as re-tanning agents in the re-tanning process to leather. The re-tanning agent could increase the shrinkage temperature of leather by up to 5 °C. Compared with the traditional method, the method utilized in this study achieved the integration of mental ions-containing wastewater treatment and waste adsorbent/adsorbates recycling.